The complementarity and comparability of climate change adaptation and mitigation. (28th September 2015) - Watkiss, Paul; Benzie, Magnus; Klein, Richard J.T.
Abstract : Both mitigation and adaptation can reduce the risks of climate change. This study reviews the complementarity and comparability between the two, looking first at the global level and then at the national‐to‐local domain. At the global level, the review finds differing definitions and viewpoints exist in the literature. Much of the economic literature reports that global mitigation and adaptation are substitutes (in economic terms). In contrast, the scientific literature considers them to be complementary (in policy terms), as they address different risks that vary temporally and spatially. The degree of complementarity and comparability therefore depends on the perspective taken, although there is a policy space where the two can overlap. However, the governance, institutional, and policy‐based literature identifies that even if a global mitigation and adaptation mix could be defined, it would be highly contentious and extremely difficult to deliver in practice. The review then considers the complementarity and comparability of mitigation and adaptation at the national‐to‐local domain, in national policy and at sector level. The review finds there is greater potential for complementarity at this scale, although possible conflicts can also exist. However, the institutional, governance, and policy literature identifies a number of barriers to practical implementation, and as a result, complementary mitigation and adaptation action is unlikely to happen autonomously. Finally, the lessons from the review are drawn together to highlight policy relevant issues and identify research gaps. WIREs Clim Change 2015, 6:541–557. doi: 10.1002/wcc.368 This article is categorized under: Integrated Assessment of Climate Change > Methods of Integrated Assessment of Climate Change The Carbon Economy and Climate Mitigation > Benefits of Mitigation Climate and Development > Sustainability and Human Well‐Being